Combination of Filtering and Switching Methods for Network Security from Pornographic Content - Hakim, Yunif Lukman; Wijayanto, Hendro (Institut Teknologi Bisnis AAS Indonesia, 2024)
The internet provides convenience in various aspects of human life. Internet penetration in Indonesia has grown by 66.5% of the total population of 278.7 million people. This shows that 185.3 million people are active internet users. Based on the report of the Ministry of Communication and Information (Kemenkominfo), it has handled negative content since 2016 to 2023 with a total of 1.9 million contents. With the most access through website media. MikroTikRouter Os as a tool used to support computer network communication, is expected to minimize access to this negative content. Configuration in MikroTik devices with Layer7 Protocol and Firewall Rules is used to prevent access to negative content from the client side. A firewall is a network security tool that monitors incoming and outgoing network traffic. The application layer that acts as a liaison between applications and network functions, manages how applications access the network, and regulates the creation of error messages is called Layer 7 Protocol. The Layer 7 Protocol configuration and firewall rules are effectively applied to Mikro Tik RB941-2ND to ward off negative pornographic content on local networks with a percentage of 87% of the 91 websites that have been tested. In particular, the test results show that this method is an effective scheme using unwanted travel with global internet usage and without using a Virtual Private Network (VPN). By using this filtering and switching technique, negative site access restrictions can be minimized. At least it can be a pioneer of a healthy internet.